Upgrade public servants in Iraqi law: Analytical study between the texts of civil service laws and government decisions - Ali Abbas, Basil; Salah Gatea, Hayder (International Journal of Psychosocial Rehabilitation, 2020)
The upgrade is a material and moral right for a public employee in Iraq, guaranteed by the law and fortifying him with some guarantees because of his direct prejudice to his living needs, and it is the goal that the employee seeks by doing his work most completely and efficiently comparable to his stay in that degree and that address, However, this right may be subject to restriction due to several factors, including temporary ones that disappear with the disappearance of the impediment and some of them are permanent. And between these and those, the research sheds light on those barriers and guarantees.